Developing standards for good educational assessment of handwriting تطوير معايير التقييم التربوي الجيّد للخط - هبة توفيق أبو عيادة (Journal of Calligraphy, 2025)
The current study aims to identify the criteria for good handwriting assessment and ways to improve and develop handwriting skills and keep pace with the developments of the era and e-learning, to come out of it with proposals and procedures that help to enable writing skills and master handwriting in a distinctive and beautiful way and invest it in developing the teaching and learning process and encouraging students to learn different types of handwriting and achieve what is expected from it and invest it to develop the educational system, through analyzing and reviewing previous research and studies and educational literature that dealt with educational assessment in a way that ensures coming out with an integrated therapeutic vision to confront the obstacles to development that dealt with educational assessment. The current study differs from previous studies in the study methodology, as the current study relies on analyzing educational literature that dealt with the topic of educational assessment through the analytical deductive method and in light of the results of previous studies and according to the researcher's vision, the current study develops a scientific vision to confront the challenges and problems of educational assessment.